MORPHOLOGICAL FEATURES OF THE ACTION OF RONCOLEUKIN ON THE INTERNAL ORGANS OF WHITE MICE (Experimental biology, 2023)
Chronic inflammatory diseases are one of the leading causes of death in the world. A number of pathological conditions are associated with chronic inflammation, such as chronic obstructive pulmonary disease, rheumatoid arthritis, metabolic syndrome, type 2 diabetes mellitus, cardiovascular, chronic kidney disease, cancer, neurodegenerative and autoimmune diseases. To address a number of issues related to this problem, reliable models of chronic inflammation are needed. A number of chemical inductors of this state are known from the literature. One of them is interleukin-2. Roncoleukin is a dosage form of recombinant human interleukin-2. To date, few studies have been presented on changes at the tissue level under the influence of IL-2. In this work, we studied the patterns of morphological changes in the lungs, liver, kidneys, spleen, and thymus of CD-1 mice under the influence of low and high doses of Roncoleukin. We have shown that the drug contributes to an increase in the mass of the spleen by 2 times and a decrease in the mass of the thymus by 1.5 times. Roncoleukin has a stimulating effect on the immunocompetent compartment, leading to cell proliferation of T-dependent zones of the spleen and thymus cortex. In the visceral organs, under its action, a picture of a chronic inflammatory process develops.
Keywords: IL-2, planimetric image analysis, chronic inflammation model, Ronkoleukin